Accommodative Performance of Children With Unilateral Amblyopia - Manh, Vivian (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. The purpose of this study was to compare the accommodative performance of the amblyopic eye of children with unilateral amblyopia to that of their nonamblyopic eye, and also to that of children without amblyopia, during both monocular and binocular viewing. METHODS. Modified Nott retinoscopy was used to measure accommodative performance of 38 subjects with unilateral amblyopia and 25 subjects with typical vision from 3 to 13 years of age during monocular and binocular viewing at target distances of 50, 33, and 25 cm. The relationship between accommodative demand and interocular difference (IOD) in accommodative error was assessed in each group. RESULTS. The mean IOD in monocular accommodative error for amblyopic subjects across all three viewing distances was 0.49 diopters (D) (95% confidence interval [CI], ±1.12 D) in the 180° meridian and 0.54 D (95% CI, ±1.27 D) in the 90° meridian, with the amblyopic eye exhibiting greater accommodative errors on average. Interocular difference in monocular accommodative error increased significantly with increasing accommodative demand; 5%, 47%, and 58% of amblyopic subjects had monocular errors in the amblyopic eye that fell outside the upper 95% confidence limit for the better eye of control subjects at viewing distances of 50, 33, and 25 cm, respectively. CONCLUSIONS. When viewing monocularly, children with unilateral amblyopia had greater mean accommodative errors in their amblyopic eyes than in their nonamblyopic eyes, and when compared with control subjects. This could lead to unintended retinal image defocus during patching therapy for amblyopia.